Impact of water stress on morpho-physiological and biochemical traits in rice genotypes (Bangladesh Journal of Botany, 2023)
Laboratory and field screening were performed in nine rice genotypes i.e., TM 12061, TM 12077, TM 12012, TM 14035, TM 16017, Senthuram, Vandhana, TKM 12 and  Anna (R) 4 to assess their drought tolerant potential. For laboratory screening, the effect of different levels of Poly Ethylene Glycol (PEG) concentration viz., -0.2, -0.4, -0.6 and -1.0 MPa on germination, shoot length and root length were studied. There was a considerable decrease in the germination potential among all the genotypes with increase in PEG concentration. The TM 12077 showed higher level of tolerance to PEG induced drought stress showing 30.8 % germination with 3.2 cm and 8.85 cm shoot and root length, respectively at higher level of concentration (1.0 MPa). In the field screening under managed stress condition, TM 12077 and TM 12012 showed higher accumulation of proline (4.15 mg/g). Chlorophyll stability index was more than 80 % in the genotypes TM 12012, TM 12077 and TM 12061. The genotype TM 14035, the varieties Anna (R) 4 and Vandhana matured early in 115 days.  Number of tillers per plant, number of panicles/sqm and yield/hectare were maximum in TM 12077.  While considering both laboratory and field screening, the genotypes TM 12077, TM 12012 and TM 12061 were found promising for water stress environment and can be utilized as donors in the drought tolerance breeding programs.  High heritability coupled with moderate to high GA as per cent of mean recorded for plant height, tillers per plant, chlorophyll stability Index and total chlorophyll content indicates the presence of additive gene effects and their improvement through direct selection.Bangladesh J. Bot. 52(4): 1041-1046, 2023 (December)